2014
DOI: 10.1016/j.kjms.2014.07.001
|View full text |Cite
|
Sign up to set email alerts
|

The impact of general anesthesia on radiofrequency ablation of hepatocellular carcinoma

Abstract: This study investigates the impact of general anesthesia (GA) on percutaneous radiofrequency ablation (RFA) of hepatocellular carcinoma (HCC). A total of 118 treatment-naïve HCC patients in Barcelona Clinic Liver Cancer curative stage were enrolled. Patients who underwent RFA with GA were designated as the GA group, and the others were identified as the non-GA group. All the percutaneous RFA procedures were performed by the same hepatologist. The GA group comprised 42 (44.1%) patients with 71 tumors (mean size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 28 publications
0
14
1
Order By: Relevance
“…It has been found that the type of anaesthesia has no effect on the survival of patients, but general anaesthesia is associated with a higher incidence of tumour recurrence [21]. For similar applications came Yuang-Hung et al by examining 118 patients [22].…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that the type of anaesthesia has no effect on the survival of patients, but general anaesthesia is associated with a higher incidence of tumour recurrence [21]. For similar applications came Yuang-Hung et al by examining 118 patients [22].…”
Section: Discussionmentioning
confidence: 99%
“…However, the large dosage of remifentanil can easily cause respiratory depression. 4,5 Dezocine is a synthetic drug of the benzmorphan group, an agonist of -opioid receptors and an antagonist of -opioid receptors. It has moderate analgesic and sedative effects and is very safe without respiratory depression.…”
Section: Introductionmentioning
confidence: 99%
“…General anesthesia undoubtedly ensures better pain control than conscious sedation and reduces patient anxiety or panic, but it is not free of risks such as myocardial infarction, stroke, and malignant hyperthermia. [23] On the other hand, conscious sedation is more painful but does not require intubation, and several relative contraindications to general anesthesia such as impairment of lung function do not preclude its use. [1] Although most percutaneous ablations of renal tumors are currently performed under conscious sedation, there is a widespread belief that general anesthesia can ensure a better outcome.…”
Section: Discussionmentioning
confidence: 99%